2020
DOI: 10.1155/2020/4676591
|View full text |Cite
|
Sign up to set email alerts
|

Spatial Pattern and Associated Factors of ANC Visits in Ethiopia: Spatial and Multilevel Modeling of Ethiopian Demographic Health Survey Data

Abstract: Background. Although there is an increase in having antenatal care (ANC), still many women lack recommended ANC contacts in Ethiopia. Therefore, this study was aimed at determining spatial patterns and associated factors of not having ANC visits using the Ethiopian Demographic and Health Survey (EDHS) 2016 data. Methods. A two-stage stratified cluster sampling technique was employed based on EDHS data from January 18 to June 27, 2016. A total of 7,462 women were included in the study. ArcGIS version 10.7 softw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 44 publications
3
11
0
Order By: Relevance
“…Finally, a weighted proportion of home delivery after ANC visit per cluster was used for spatial autocorrelation analysis and hotspot analysis. For spatial scan statistics number of women who had home delivery after ANC visit and the number of women who had institutional delivery were considered as cases and controls respectively to fit the Bernoulli model [ 12 ].…”
Section: Methodsmentioning
confidence: 99%
“…Finally, a weighted proportion of home delivery after ANC visit per cluster was used for spatial autocorrelation analysis and hotspot analysis. For spatial scan statistics number of women who had home delivery after ANC visit and the number of women who had institutional delivery were considered as cases and controls respectively to fit the Bernoulli model [ 12 ].…”
Section: Methodsmentioning
confidence: 99%
“…Studies have demonstrated that sociodemographic factors such as age, wealth index, geographical location, educational status, husband occupation, marital status, and socioeconomic status are significantly associated with ANC utilization [2,4,5,[9][10][11][12]. For instance, a cross-sectional study conducted in Nigeria by Fagbamigbe and Idemudia [4] found a five-fold increase in ANC utilization among women in the wealthiest quintile.…”
Section: Introductionmentioning
confidence: 99%
“…For instance, in Ethiopia, a relatively higher utilization was found in Addis Ababa [ 31 - 37 ], Dire Dawa [ 31 , 34 - 37 ], Tigray [ 31 , 33 - 39 ], and Harari [ 31 , 33 , 35 , 36 ]. A relatively low utilization was found in regions of Somali [ 31 , 33 , 34 , 36 , 37 , 39 ], Afar [ 31 , 33 - 35 , 37 ], Oromia [ 32 , 33 , 35 , 36 , 39 ], most of Amhara [ 33 - 35 , 37 , 40 ], Gambela [ 32 , 33 , 37 , 39 ], Benishangul Gumuz [ 34 , 35 ], and parts of Southern Nations Nationalities and Peoples Region [ 32 , 34 - 36 , 39 , 40 ]. Similarly, a significant north-south divide in the likelihood of maternal health care utilization was reported in Nigeria.…”
Section: Resultsmentioning
confidence: 99%
“…Inequality in maternal health care utilization was also identified at a national level. For instance, in Ethiopia, a relatively higher utilization was found in Addis Ababa [31][32][33][34][35][36][37], Dire Dawa [31,[34][35][36][37], Tigray [31,[33][34][35][36][37][38][39], and Harari [31,33,35,36]. A relatively low utilization was found in regions of Somali [31,33,34,36,37,39], Afar [31,[33][34][35]37], Oromia [32,33,35,36,39], most of Amhara [33][34][35]37,40], Gambela [32,33,37,39], Benishangul Gumuz…”
Section: Identifying Inequalities In Maternal Health Care Utilizationmentioning
confidence: 99%